Optimizing the Search for Cost Deviation Sources - Demski, Joel S. (Management Science, 1970)
The typical statistical cost control model determines when a cost deviation is significant, but does not determine the optimum search procedure for restoring the process to a state of control. This search procedure is important because any given cost deviation may be the result of a number of individual causes and each cause requires different search activity. A model is developed (and subsequently extended) for determining the optimum sequence in which to examine the various possible causes.